Distribution of CD44 messenger RNA in archival paraffin wax embedded tumours and normal tissues viewed by in situ hybridisation. Issue 3 (June 1996) - Gorham, H; Sugino, T; Bolodeoku, J; Yoshida, K; Goodison, S; Tarin, D
Abstract : Aims —We have previously demonstrated the abnormal localisation of expression of the CD44 gene in carcinoma cells in cryostat sections of fresh frozen tumour tissues, using radioactive in situ hybridisation (RISH). In order to facilitate further analysis of the expression of this gene in a wider range of neoplastic and non-neoplastic conditions, we have developed a technique which can visualise its low copy number transcripts in archival paraffin wax embedded specimens. Methods — 35 S labelled riboprobes complementary to transcripts from the standard (CD44s) and variant (CD44v) regions of the gene were used on paraffin wax embedded sections of tumours and corresponding normal tissues of the colon, breast and uterine cervix. Results —Elevated levels of signals for CD44s and CD44v transcripts were observed in carcinoma cells relative to their non-neoplastic counterparts in all tissues examined. Conclusion —This method permits easy access to material which can be selected for suitability, handled at room temperature without degradation and relied upon to show good histological detail. Comparison of the results with those on frozen tissues showed similar distributions of signals. Furthermore, the resolution and morphological detail was improved in paraffin wax sections.